Prospective case-control study of cardiovascular abnormalities six months following mild COVID-19 in healthcare workers. (13th July 2021) - Joy, G; Artico, J; Kurdi, H; Lau, C; Adam, RD; Menacho, KM; Pierce, I; Captur, G; Davies, R; Schelbert, EB; Fontana, M; Kellman, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Barts Charity UCLH Charity OnBehalf: COVIDsortium Background: Recent CMR studies have reported cardiac abnormalities after COVID-19 are common, even after mild, non-hospitalised illness with evidence of ongoing myocardial inflammation. Such a prevalence of chronic myocarditis after mild disease has prompted societal concerns in diverse domains, and suggests that screening should be considered post COVID-19, even in asymptomatic individuals. Cardiovascular magnetic resonance (CMR) has proven utility for diagnosis in patients with COVID-19 infection and elevated troponin from unclear causes by measuring cardiac structure, function, myocardial scar (late gadolinium enhancement) and oedema (T1 and T2 mapping). Objectives: We aimed to determine the prevalence and extent of late cardiac and cardiovascular sequelae after mild non-hospitalised SARS-CoV-2 infection. Methods: Participants were recruited from COVIDsortium, a three-hospital prospective study of 731 healthcare workers who underwent first wave weekly symptom, PCR and serology assessment over 4 months, with seroconversion in 21.5% (n = 157). At 6 months post infection, 74 seropositive and 75 age-, sex-, ethnicity-matched seronegative controls were recruited for cardiovascular phenotyping (comprehensive phantom-calibrated Cardiovascular Magnetic Resonance and blood biomarkers). Analysis was blinded, using objective AI analytics where available. Results: 149 subjects (mean age 37 years, range 18-63, 58% female) were recruited. Seropositive infections had been mild with case definition/non-case definition/asymptomatic disease in 45(61%), 18(24%) and 11(15%) with one person hospitalised (for 2 days). Between seropositive and seronegative groups, there were no differences in cardiac structure (left ventricular volumes, mass; atrial area), function (ejection fraction, global longitudinal shortening, aortic distensibility), tissue characterisation (T1, T2, ECV mapping, late gadolinium enhancement) or biomarkers (troponin, NT-proBNP). With abnormal defined by the 75 seronegatives (2 standard deviations from mean, e.g. EF < 54%, septal T1 > 1072ms, septal T2 > 52.4ms), individuals had abnormalities including reduced EF (n = 2, minimum 50%), T1 elevation (n = 6), T2 elevation (n = 9), LGE (n = 13, median 1%, max 5% of myocardium), biomarker elevation (borderline troponin elevation in 4; all NT-proBNP normal). These were distributed equally between seropositive and seronegative individuals. Conclusions: Cardiovascular abnormalities are no more common in seropositive vs seronegative otherwise healthy, workforce representative individuals 6 months post mild SARS-CoV-2 infection. Our study provides societal reassurance for the cardiovascular health of working-aged individuals with convalescence from mild SARS-CoV-2. Screening asymptomatic individuals following mild diseases is not indicated.